Utilization of the Recitation Method in Increasing Learning Intensity and Student Learning Outcomes in the Subject of Moral Creeds in Class VII MTs S. Hasan Yamani - Firmansyah; Abdul Halik; Ahdar; Usman; Kaharuddin (Universitas Muhammadiyah Palu, 2025)
This research aims to find out how the recitation method is used to increase learning intensity and student learning outcomes in the Moral Creed subject in Class VII MTs S. Hasan Yamani. The method used in this research is classroom action research or known as classroom action research. Data collection techniques in this research used interview, observation and documentation techniques. The instruments used in this research are observation guidelines and assessment of learning outcomes. Meanwhile, this research uses a descriptive analysis method using a list of students' cognitive values. The results of this research explain that the recitation method is able to increase the intensity of student learning seen from the enthusiasm, motivation, activeness of students in the learning process, and improve student learning outcomes in the Aqidah Akhlak subject. This can be illustrated from the results of the grades achieved by students which can be seen from The increase before the research (pre-cycle) was with an average class score of 63.84, while in the first cycle the class average score was 81.08 and in the second cycle the class average increased to 86.96 with a success percentage reaching 100% above the KKM. 70. After the implementation of cycle I and cycle II, it can be seen that with the use of the Recitation Method, the intensity and results of student learning in the Aqidah AKHlak subject have increased compared to before the implementation of the Recitation method, because by using and utilizing this Recitation Method, each student can pay more attention and be active in learning process and fostering a competitive spirit in learning. The implication of this research is that increasing learning outcomes through the Recitation Method can be used as an alternative teaching and learning activity by teachers and Madrasahs in order to increase the intensity and learning outcomes of students at MTs S. Hasan Yamani in the subject of Aqidah Akhlak.